Views of Students on Islamic Financial Technology: A Study on State Universities in Bandung - Firmansyah, Egi Arvian; Manaf, Umar Ibrahim (Economica: Jurnal Ekonomi Islam, 2020)
Abstract: Fintech has developed into a new paradigm with great potential worldwide, including in Indonesia. Angsur is one of the Islamic fintech firms with university students as its target market. This study uses primary data obtained through a questionnaire disseminated to 316 undergraduate economics and business students at three state universities in Bandung. We selected Bandung as it is also known as an educational city with many well-known universities. This study uses the Mann-Whitney test to identify the mean difference in knowledge of Islamic fintech products and Angsur brand awareness of students based on age, gender, university, and monthly expenses. In addition, we use multiple linear regression to investigate the influence of demographic factors on Islamic fintech product knowledge and Angsur brand awareness. The result of this study shows that only university origin has a significant difference in Angsur brand awareness. Demographic factors do not affect respondents’ knowledge about Islamic fintech products and Angsur brand awareness. Besides, the knowledge about Islamic fintech products and Angsur brand awareness is still relatively low. Materials or courses about Islamic fintech are not available in the academic syllabus of the respondents. Thus, to improve the Islamic financial literacy of university students, it is necessary to add Islamic economic materials to the curriculum at the university level.Abstrak: Fintech telah tumbuh dan berkembang menjadi paradigma baru dengan potensi yang besar di seluruh dunia, termasuk di Indonesia. Angsur merupakan salah satu perusahaan fintech Syariah dengan target pasar mahasiswa. Penelitian ini menggunakan data primer yang didapat melalui kuesioner terhadap 316 mahasiswa sarjana di fakultas ekonomi dan bisnis di tiga perguruan tinggi negeri di Kota Bandung. Kota Bandung juga dikenal salah satunya sebagai kota pendidikan dan banyak perguruan tinggi negeri ternama. Penelitian ini menggunakan statistik deskriptif untuk melihat tingkat pengetahuan produk fintech Syariah dan kesadaran merek Angsur mahasiswa dan opini mahasiswa terhadap materi fintech Syariah dalam silabus perkuliahan. Penelitian ini menggunakan uji Mann-Whitney untuk melihat perbedaan rata-rata pengetahuan produk fintech Syariah dan kesadaran merek Angsur mahasiswa berdasarkan usia, jenis kelamin, asal universitas, dan pengeluaran per bulan. Kami menggunakan regresi linear berganda untuk melihat pengaruh faktor demografis terhadap pengetahuan produk fintech Syariah dan kesadaran merek Angsur mahasiswa. Hasil penelitian menunjukkan bahwa hanya asal universitas yang memiliki perbedaan yang signifikan terhadap kesadaran merek Angsur. Faktor demografis tidak berpengaruh terhadap pengetahuan produk fintech Syariah dan kesadaran merek Angsur mahasiswa. Tingkat pengetahuan produk fintech Syariah dan kesadaran terhadap merek Angsur masih rendah, dan pelajaran tentang fintech Syariah tidak terdapat dalam silabus akademik perkuliahan. Sehingga, untuk meningkatkan literasi keuangan Syariah para mahasiswa, diperlukan edukasi dan penambahkan materi ekonomi Syariah dalam kurikulum di berbagai perguruan tinggi.